Pemanfaatan Biotron Untuk Perbaikan Sifat Tanah di Lahan Marginal: Model Pemberdayaan Petani Desa Paya Gaboh - Zurrahmi Wirda; Rosnina; Usnawiyah; Ekamaida; Utomo Pasa; Fikri Anggara; Della Al Isra (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Utilization of biotron to improve soil properties in marginal lands: a model for empowering farmers in paya gaboh village. Paya Gaboh Village has marginal land characteristics with a predominance of inceptisol soil and low fertility levels, resulting in suboptimal agricultural productivity. This community service activity aims to improve farmers' knowledge and skills in utilizing agro-industrial waste to produce three-in-one biochar as an environmentally friendly soil conditioner. The implementation methods included counseling, training in the production of three-in-one biochar, and direct application to agricultural land. The raw materials for biochar came from agricultural waste such as bagasse, empty palm oil fruit bunches, and rice husks, which were processed through pyrolysis and activation, then enriched with liquid organic fertilizer and microbial consortia. The results of the activity showed an increase in community understanding and active participation in waste management and the application of soil conditioner technology. Three-in-one biochar has the potential to improve soil physical properties and support sustainable agriculture on marginal land.